Tebat Rasau Geopark: Ethnobiology and Ethnogeology of a Pleistocene River in Belitung, Indonesia - Ary Prihardhyanto Keim; Fithrorozi Fithrorozi; Tukul Rameyo Adi; R. Indarjani; Fauzi Akbar; Yudi Amsoni; Ida Farida Hasanah; Wawan Sujarwo (The Ethnobiological Society of Indonesia, 2021)
Belitung is an island on the south eastern coast of Sumatra, Indonesia. Geologically, Belitung is an continental island and during Pleistocene was united with Sumatra and Borneo to form a subcontinent named Sundaland indicated by the existence of an archaic Pleistocene river located in Tebat Rasau in the East Belitung Regency with the presence of Asiatic arowana (Scleropages formosus) and non-poisonous freshwater pufferfish from the genus Pao, which is identified here as resembling Pao hilgendorfii. The existence of these biota strengthening the concept of Sundaland and has put Belitung tributaries closer to mainland Borneo’s river system rather than that of Sumatra’s. Fascinating discoveries found in this current study are the fact that the people of Tebat Rasau acknowledge based on the presence of the Asiatic arowana and non-poisonous pufferfish about the union of Belitung with the mainland Borneo and Sumatra in the past long before the concept of Sundaland itself was formulated and published. This knowledge has put the people of Tebat Rasau more aware on the conservation of the area and fully supports the appointment of the Tebat Rasau vicinity as a National Geopark. The local products have also produced from the vicinity including the well-known herbal tea from the leaves of Pelawan tree (Tristaniopsis merguensis; Myrtaceae) known as “Pelawan Tea”.